The Perlocutionary Acts of the Characters in Wonder a Novel by R.J. Palacio - Prami Wahyudiantari, Ni Wayan (e-Journal of Linguistics; Vol 15 No 1 (2021): ejl-January, 2020)
This research discusses the use of perlocutionary acts uttered by the characters in Wonder a novel by R.J. Palacio. It explores how the acts of perlocutionary are conveyed by the characters in the whole novel. The purpose of this study are to find the type of perlocutionary acts uttered by the main characters, the intended meaning of utterances, and the character’s purposes in using such perlocutionary acts. This research applies pragmatics theory about speech acts to analyze the use of perlocutionary acts in conversations. This study is qualitative research and it uses document as the source of the data that is Wonder a novel by R.J. Palacio. The result of this study show that there are three types of perlocutionary uttered by the characters. The types of the illocutionary acts are verbal perlocutionary acts, non verbal perlocutionary acts and verbal non verbal perlocutionary acts. Those utterances have the intended meanings that are influenced by the context of situation in every phenomenon .